Embedding chiropractic in Indigenous Health Care Organisations: applying the normalisation process model - Polus Barbara I; Paterson Charlotte; van Rotterdam Joan; Vindigni Dein (BMC, 2012)
Abstract Background Improving the health of Indigenous Australians remains a major challenge. A chiropractic service was established to evaluate this treatment option for musculoskeletal illness in rural Indigenous communities, based on the philosophy of keeping the community involved in all the phases of development, implementation, and evaluation. The development and integration of this service has experienced many difficulties with referrals, funding and building sustainability. Evaluation of the program was a key aspect of its implementation, requiring an appropriate process to identify specific problems and formulate solutions to improve the service. Methods We used the normalisation process model (May 2006) to order the data collected in consultation meetings and to inform our strategy and actions. The normalisation process model provided us with a structure for organising consultation meeting data and helped prioritise tasks. Our data was analysed as it applied to each dimension of the model, noting aspects that the model did not encompass. During this process we reworded the dimensions into more everyday terminology. The final analysis focused on to what extent the model helped us to prioritise and systematise our tasks and plans. Results We used the model to consider ways to promote the chiropractic service, to enhance relationships and interactions between clinicians and procedures within the health service, and to avoid disruption of the existing service. We identified ways in which chiropractors can become trusted team members who have acceptable and recognised knowledge and skills. We also developed strategies that should result in chiropractic practitioners finding a place within a complex occupational web, by being seen as similar to well-known occupations such as physiotherapy. Interestingly, one dimension identified by our data, which we have labelled 'emancipatory', was absent from the model. Conclusions The normalisation process model has resulted in a number of new insights and questions. We have now established thriving weekly chiropractic clinics staffed by a team of volunteer chiropractors. We identified an 'emancipatory' dimension that requires further study. We provide a worked example of using this model to establish, integrate and evaluate a chiropractic service in an Indigenous Australian community.